Utility Of The Multivariate Approach In Predicting β-Thalassemia Intermedia Or β-Thalassemia Major Types In Iranian Patients. (October 2013) - Banan, Mehdi; Bayat, Hadi; Namdar-Aligoodarzi, Pegah; Azarkeivan, Azita; Kamali, Koorosh; Daneshmand, Parvaneh; Zaker-Kandjani, Behzad; Najmabadi, Hossein
<x xml:space="preserve">Abstract</x> Recently, five genetic modifiers [β-globin mutations, coinheritance of α-thalassemia (α-thal), XmnI polymorphism and single nucleotide polymorphisms (SNPs) in the BCL11A and HBS1L-MYB loci] were used to predict the β-thal major (β-TM) or β-thal intermedia (β-TI) types in 106 French patients with 83.2% accuracy. The dichotomous grouping was based on the age when the patient received his/her first transfusion (4 years). Here, a similar study was conducted in a cohort of 306 Iranian β-thal patients having distinct β-globin mutations and minor allele frequencies of key SNPs in these loci. Multivariate regression analyses and a simple scoring system were used to predict the β-TM/β-TI types using three scenarios: 1) when considering only the severe β-TM and the mild β-TI cases, 2) using clinical parameters for β-thal typing, and 3) using age at first transfusion as the basis for classification. Using these scenarios, the β-thal types could be correctly predicted in 77.6, 75.5 and 68.0% of cases, respectively.